A storm on the Gyraean rocks and the death of Ajax the Lesser (Archaeologia Adriatica, 2020)
Myth has it that Ajax the Lesser (son of Oileus and also known as Locrian) was killed in a storm on the Gyraean Rocks. Scholars have been trying to locate the rocks ever since Classical Antiquity: from Euboea and Cape Caphareus across Andros and Tênos all the way to Myconos. Their location has remained unknown not so much because it was part of a mythical rather than real geography but rather because with time it has faded into oblivion. Ajax the Lesser was a "threshold creature", one of the figures that symbolises the crossing from this world into the otherworld, who later entered heroic epics as a "historical" hero who fought at Troy, known for his desecration and crimes for which the gods punished him by sending a storm against him as he returned from Troy.
Keywords: Ajax the Lesser – son of Oileus – Locrian; Gyraean Rocks; Akra Gyreon; Andros; Tênos; Myconos; threshold into the otherworld